Molecular medicine-based IBD treatment strategies—we take it personally! - Hentschel, Viktoria; Klaus, Jochen (Frontiers in Gastroenterology, 2023)
In light of potentially aggressive disease courses of either IBD entity -CD and UC -marked by frequent flare-ups or non-subsiding inflammatory activity, effective immunosuppression is key to prevent progressive tissue destruction and permanent disability. However, on the other hand, over-treating patients with a high probability of an indolent disease course is to be avoided. To solve this therapeutic dichotomy, there is a pressing need for a reliable distinction of patients based on their biosignature to rate their individual prognosis and likelihood of response to a given therapy. This need for pinpoint therapeutic strategies is addressed by the concepts of PreM and the more stringently defined PerM. In this review we summarize the most pivotal study results published so far in the field of individualized IBD care with a special focus on molecular diagnostics in conjunction with their applicability in the clinical setting.